KEJADIAN KEPUTIHAN PADA MAHASISWI FAKULTAS ILMU KEGURUAN UNIVERSITAS MUHAMMADIYAH SAMPIT TAHUN 2023 - Puspita Sari Pribadi; Nera Saputri (LPSDI Bina Patria, 2024)
Background: The impact of abnormal vaginal discharge is an infection with germs o that enter the vagina, causing vaginal discharge that progresses to a more severe stage and is at risk for cases of Sexually Transmitted Infections (STI). Objectives: Knowing the Relationship between Knowledge of Vaginal Hygiene and Incidence of Leucorrhoea in Female Teacher Training Faculty, Sampit Muhammadiyah University in 2023. Method: This research is a quantitative analytic research with a cross sectional research design, the sample used in this study was 82 female students with accidental sampling technique. Result : The majority of vaginal hygiene knowledge is in the good category as many as 55 respondents, and in the sufficient category as many as 27 respondents. The majority of female students who experienced pathological vaginal discharge were 42 respondents and female students who experienced physiological vaginal discharge were 40 respondents. Conclusion : There is a significant relationship between knowledge of vaginal hygiene and the incidence of vaginal discharge in female students of the Teaching Sciences Faculty of Muhammadiyah Sampit University in 2023